Optimal design of unbounded 2D composite materials with circular inclusions of different radii - Svetlana Lebed; Sergei Rogosin (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2008)
Optimal design problem for 2D composite materials with different circular inclusions is studied on the base of the potential method combined with functional equation method. Exact geometric description of the optimal distribution of the inclusions is determined.